2016
DOI: 10.1016/j.gloplacha.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Review: Potential catastrophic reduction of sea ice in the western Arctic Ocean: Its impact on biogeochemical cycles and marine ecosystems

Abstract: a b s t r a c tThe reduction of sea ice in the Arctic Ocean, which has progressed more rapidly than previously predicted, has the potential to cause multiple environmental stresses, including warming, acidification, and strengthened stratification of the ocean. Observational studies have been undertaken to detect the impacts on biogeochemical cycles and marine ecosystems of these environmental stresses in the Arctic Ocean. Satellite analyses show that the reduction of sea ice has been especially great in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 175 publications
(251 reference statements)
0
62
0
Order By: Relevance
“…High marine production in the Chukchi Sea of up to 400 g C m −2 y −1 in part is thought to reflect the high nutrient fluxes by the BSI (Walsh and Dieterle, 1994;Sakshaug, 2004). A recent enhancement of biological productivity and the biological pump in the Beaufort and Chukchi seas has been associated with the retreat of sea ice (summarized by Harada, 2016). This phenomenon is attributed to an increase in irradiance in the water column (Frey et al, 2011;Lee and Whitledge, 2005), wind-induced mixing that replenishes sea surface nutrients , and their combination (Nishino et al, 2009).…”
Section: Oceanographic Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…High marine production in the Chukchi Sea of up to 400 g C m −2 y −1 in part is thought to reflect the high nutrient fluxes by the BSI (Walsh and Dieterle, 1994;Sakshaug, 2004). A recent enhancement of biological productivity and the biological pump in the Beaufort and Chukchi seas has been associated with the retreat of sea ice (summarized by Harada, 2016). This phenomenon is attributed to an increase in irradiance in the water column (Frey et al, 2011;Lee and Whitledge, 2005), wind-induced mixing that replenishes sea surface nutrients , and their combination (Nishino et al, 2009).…”
Section: Oceanographic Settingsmentioning
confidence: 99%
“…The Arctic currently faces rapid climate change caused by global warming (e.g., Screen and Simmonds, 2010;Harada, 2016). Changes in the current system of the Arctic Ocean regulate the state of Arctic sea ice and are involved in global processes via ice albedo feedback and the delivery of freshwater to the North Atlantic Ocean (Miller et al, 2010;Screen and Simmonds, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the climate change induced alteration in the sea-ice cover influence biogeochemical cycles in the western Arctic (Harada, 2016). Further, arctic benthic oxygen flux model by Bourgeois et al (2017) showed a better fit when benthic chlorophyll data, indicating surface primary production patterns, were taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s the Arctic climate has warmed at least twice as fast as the global mean (Francis and Vavrus, 2015) with associated dramatic declines in sea ice cover (Kwok and Cunnigham, 2015), terrestrial snow pack (Derksen et al, 2015) and 5 permafrost (Lawrence et al, 2015), coincident with increase in continental freshwater discharge into the Arctic Ocean (Carmack et al, 2016) and changes in the biochemical cycle (Shakhova et al 2007;Harada, 2016). These changes have strong socio-economic and environmental impacts.…”
Section: Introductionmentioning
confidence: 99%